2022
DOI: 10.1038/s41598-022-08999-z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, antifungal, and aphicidal activity of the triterpenoids spinasterol and 22,23-dihydrospinasterol from leaves of Citrullus colocynthis L.

Abstract: Terpenoids from natural plant sources are valuable for their diverse biological activities that have important roles in the medical and agrochemical industries. In this study, we assessed the antioxidant, antifungal, and aphicidal activities of a mixture of spinasterol and 22,23-dihydrospinasterol from the leaves of Citrullus colocynthis. We used 1,1-diphenyl-2-picrylhydrazyl (DPPH) to assess antioxidant activity, and we measured antifungal activity using mycelium growth inhibition assays with three pathogenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…susceptibility to C. colocynthis extracts greatly relies on the species and, within the same species, on the extraction solvent [ 10 ]. On the other side, if antifungal properties of both botanicals and pure compounds isolated from C. colocynthis have been variously described against some phytopathogens (for example, a mixture of spinasterol and 22,23-dihydrospinasterol obtained from the leaves [ 49 ], our observations didn’t provide any significant cue with respect to the aflatoxigenic species selected in this study. However, findings showing the absence of any antifungal or fungistatic potential of extracts on the A. flavus mycelium long-term growth weren’t completely unexpected: in fact, various studies have reported that several compounds, both synthetic and natural, are effective in lowering AF production without apparently interfering with the fungal hyphae elongation or mycelium development [ 13 , 50 , 51 , 52 , 53 ]; this phenomenon has been ascribed to the induction of physiological responses that possibly affect hyphal branching but not apex elongation, and thus result in unaltered colony marginal expansion—which is necessary for efficient colonization and utilization of the substrate.…”
Section: Discussionmentioning
confidence: 74%
“…susceptibility to C. colocynthis extracts greatly relies on the species and, within the same species, on the extraction solvent [ 10 ]. On the other side, if antifungal properties of both botanicals and pure compounds isolated from C. colocynthis have been variously described against some phytopathogens (for example, a mixture of spinasterol and 22,23-dihydrospinasterol obtained from the leaves [ 49 ], our observations didn’t provide any significant cue with respect to the aflatoxigenic species selected in this study. However, findings showing the absence of any antifungal or fungistatic potential of extracts on the A. flavus mycelium long-term growth weren’t completely unexpected: in fact, various studies have reported that several compounds, both synthetic and natural, are effective in lowering AF production without apparently interfering with the fungal hyphae elongation or mycelium development [ 13 , 50 , 51 , 52 , 53 ]; this phenomenon has been ascribed to the induction of physiological responses that possibly affect hyphal branching but not apex elongation, and thus result in unaltered colony marginal expansion—which is necessary for efficient colonization and utilization of the substrate.…”
Section: Discussionmentioning
confidence: 74%
“…It is generally assumed that phytosterols play a key role in stabilizing the cell membranes in plants (as cholesterol does in animals) [ 30 ]; however, the chemical composition of sterols from XYMJ tea tree leaves remains elusive. Spinasterol and 22,23-dihydrospinasterol are triterpenoids that are produced by a number of plants [ 31 ]. An extract from the leaves of Mukia maderaspatana indicated that spinasterol and 22,23-dihydrospinasterol have potential antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-based in vitro studies and in animal experiments, α-spinasterol showed antiinflammatory and antioxidant activities through multiple mechanisms (Figure 3). Even at a very low concentration (0.8 μg/mL), spinasterol and 22,23-dihydrospinasterol showed significant antioxidant activity (Ahmed et al, 2022).…”
Section: Antiinflammatory and Antioxidant Activitiesmentioning
confidence: 97%